Sublethal effects of a juvenile hormone analog, Pyriproxyfen on demographic parameters of non-target predator, Hippodamia convergens Guerin-Meneville (Coleoptera Coccinellidae) - Iftikhar, Ayesha (Ecotoxicology (London, England), 2020)
Insect predators, in general, play an important role in regulating pest populations in agricultural systems, but may be negatively affected by pesticides used in pest management. Convergent lady beetle, Hippodamia convergens Guerin-Meneville (Coleoptera: Coccinellidae) is known as an important biological control agent of soft-bodied insect pests. The development of Integrated Pest Management (IPM) program against insect pests requires an assessment of the side effect of insecticides on biological control agents. In the present work, we assessed the sublethal effects of an insect growth regulator, Pyriproxyfen (juvenile hormone mimic) on a common aphidophagous beetle, H. convergens by computing its demographic parameters through age-stage, two-sex life table theory. Present results showed that sublethal (LC10 and LC30) concentrations of tested insecticide prolonged the pre-adult developmental duration while adult longevity, fecundity and fertility were reduced following treatment compared with control. However, total pre-ovipositional period (TPOP) was declined with the increasing trend of insecticide concentration. In additions, population growth parameters such as intrinsic rate of increase r, finite rate of increase λ and net reproductive rate R0 were dramatically reduced in H. convergens population when they treated with sublethal concentrations pyriproxyfen. Therefore, the results obtained through this study reflected that pyriproxyfen impairs the population growth parameters and could reduce the biological services provided by H. convergens. Thus, more attention should be paid to the use of this insecticide in IPM program